The Harmful Effects of Welding Fumes on Human Dental Enamel-A Microhardness Analysis - Catrinel Ștefania Petrovici; Răzvan Alexandru Grăjdeanu; Adina Petcu; Monica Vasile; Beatrice Marcela Severin; Doru Florin Petrovici; Lucian Cristian Petcu (MDPI AG, 2024)
Introduction: Over the years, welding fumes' harmful effects have been demonstrated countless times in the scientific literature. Recently, studies in the field have shown an increasing interest in the negative consequences that these fumes may have on the tissues of the oral cavity. Materials & method: The current study aimed to investigate the impact that welding fumes have on the structure of human dental enamel by analyzing the microhardness of the dental enamel in 15 extracted human teeth, after various exposure times, using the Vickers method. Results: The results obtained after 48, 96, 168, and 336 h of direct exposure of the extracted specimens to the welding fumes show a statistically significant increase in the depreciation of the dental enamel's microhardness, related to the duration of exposure (p < 0.05). An average of 305 Vickers units was observed at the longest exposure time, 336 h, in the present study, whereas in the control group, the microhardness analysis showed an average of 327 Vickers units.